Rainbow Connection pada Graf Siput, Graf Tunas Kelapa dan Graf Lotus - Indi Izzah Makhfduloh; Dafik Dafik; R Adawiyah (jcgant, 2023)
Graph colouring is giving colour to a set of vertices and a set of edges on a graph. The condition for colouring a graph is that each colour is different for each neighbouring graph member. Graph colouring can be done by mapping a different colour to each vertex or edge. Rainbow colouring is part of the rainbow-connected edge colouring, where every graph G has a rainbow path. A rainbow path in graph G is formed if two vertices on graph G do not have the same colour. The minimum number of colours in a rainbow-connected graph is called the rainbow connection number denoted by rc(G). The graphs used in this study are the snail graph (Sn), the coconut shoot graph (CRn,m) and the lotus graph (Lon).